In her tracks - Dugoni, Robert (Dugoni, Robert. Tracy Crosswhite series., 2021)
Reopening the cold case of an abducted child whose parents were once prime suspects, detective Tracy Crosswhite is simultaneously partnered with Kinsington Rowe to investigate a jogger's disappearance from a North Seattle trail.